2003
DOI: 10.1046/j.1365-2435.2003.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Are bacteria more like plants or animals? Growth rate and resource dependence of bacterial C : N : P stoichiometry

Abstract: Summary 1.We examined the relative importance of resource composition (carbon : phosphorus molar ratios which varied between 9 and 933) and growth rate (0·5-1·5 h − 1 ) to biomass carbon : nitrogen : phosphorus stoichiometry and nucleic acid content in Escherichia coli grown in chemostats, and in other heterotrophic prokaryotes using published literature. 2. Escherichia coli RNA content and the contribution of RNA-P to total cellular P increased with increasing growth rate at all supply C : P ratios. Growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
262
4
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(290 citation statements)
references
References 46 publications
15
262
4
1
Order By: Relevance
“…4C, p Ͻ 0.05, R and P contents with growth rate in the N-limited experiment should be interpreted cautiously, since our N-limited growth conditions did not induce a very wide range of growth rates in the animals, especially when compared to the P-limited case. Our data on Daphnia in the N-limited experiment have been placed in a broader context in the analyses of , who noted a decoupling of growth, RNA, and P contents in other biota under certain conditions: in bacteria when substrate C : P ratios are low (Makino et al 2003), under very low food conditions in Daphnia (Sterner unpubl. data), as well as in cyanobacteria and eukaryotic algae (Rhee 1978;Healey 1985).…”
Section: Discussionmentioning
confidence: 96%
“…4C, p Ͻ 0.05, R and P contents with growth rate in the N-limited experiment should be interpreted cautiously, since our N-limited growth conditions did not induce a very wide range of growth rates in the animals, especially when compared to the P-limited case. Our data on Daphnia in the N-limited experiment have been placed in a broader context in the analyses of , who noted a decoupling of growth, RNA, and P contents in other biota under certain conditions: in bacteria when substrate C : P ratios are low (Makino et al 2003), under very low food conditions in Daphnia (Sterner unpubl. data), as well as in cyanobacteria and eukaryotic algae (Rhee 1978;Healey 1985).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, strong couplings between l, RNA and P have been documented in various daphnids (DeMott et al, 1998;Vrede, Andersen & Hessen, 1999;Acharya, Kyle & Elser, 2004), the bacterium Escherichia coli (Makino et al, 2003), cyanobacteria (Lepp & Schmidt, 1998), yeast (Aiking & Tempest, 1976), algae (Rhee, 1978) and other biota . While there are consistent general patterns within species and groups of species, considerable variation in the relationships of RNA and P contents with growth does exist among taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Past work has shown that heterotrophic bacteria, a group of organisms that process terrestrial inputs of organic carbon, nitrogen (N) and phosphorus (P) , are C-poor and P-rich (Makino et al, 2003) relative to terrestrial inputs characterized by high C:P ratios. As a result, bacterial assemblages in freshwater ecosystems should experience elemental imbalance and act as efficient exporters of organic carbon to downstream ecosystems.…”
mentioning
confidence: 99%
“…The range of P content measured in the assemblage cultures was nearly equal to the range of existing data in the literature, particularly for P relative to dry mass (Supplementary Table 6). Single-cell measurements from plankton environments indicated the potential for even lower phosphorus quotas (Norland et al, 1995;Cotner et al, 2010), although many of those cells may not be actively growing, potentially decreasing their demand for P-rich RNA, where much of the P resides in bacterial cells (Makino et al, 2003). The P relative to dry mass values measured here were lower than those reported for a bacterium grown in the absence of added phosphate and high concentrations of arsenate (0.012% of dry mass as P, Wolfe-Simon et al, 2010).…”
mentioning
confidence: 99%